Impact of entrepreneurial education policies on reducing bullying among university students with anatomical and physiological disabilities: review - Rababah, Eman; Hamdan, Esra; Halalsheh, Raed; Rababah, Bayan (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines the impact of entrepreneurial education (EE) policies on reducing bullying (Tanamor) among university students with anatomical and physiological disabilities and special needs. Using a descriptive approach grounded in theoretical literature, the study identifies positive outcomes, such as enhanced self-confidence and peer respect among students with disabilities. It highlights the role of EE in creating inclusive environments that mitigate bullying. The review underscores the necessity for further research, including longitudinal studies to understand the long-term impact of these educational strategies. The findings advocate for integrating EE into university policies to support the well-being and academic success of students with disabilities.